2014
DOI: 10.4028/www.scientific.net/msf.778-780.226
|View full text |Cite
|
Sign up to set email alerts
|

Heteroepitaxial CVD Growth of 3C-SiC on Diamond Substrate

Abstract: This work presents the successful CVD heteroepitaxial growth of 3C-SiC on diamond (100) substrates. When performing a direct SiC growth at 1500°C on such substrate, it leads to polycrystalline deposit. The use of a substrate pretreatment involving silicon deposition allows forming a more continuous and smoother layer. Electron BackScatter Diffraction and Transmission Electron Microscopy all revealed that the 3C-SiC layer grown on the (100) diamond substrate is monocrystalline and well oriented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In this work, we demonstrate that SiC can be grown heteroepitaxially on single-crystal diamond, producing a coherent and seemingly strain-free interface in localized regions. This builds on a Si surface termination procedure developed in earlier work and may explain the observed benefit of Si-rich deposition prior to the CVD growth of SiC on diamond . The absence of measured strain here is remarkable given the approximate 22% lattice mismatch of SiC relative to diamond.…”
Section: Epitaxial Silicon Carbide On Diamondmentioning
confidence: 58%
See 1 more Smart Citation
“…In this work, we demonstrate that SiC can be grown heteroepitaxially on single-crystal diamond, producing a coherent and seemingly strain-free interface in localized regions. This builds on a Si surface termination procedure developed in earlier work and may explain the observed benefit of Si-rich deposition prior to the CVD growth of SiC on diamond . The absence of measured strain here is remarkable given the approximate 22% lattice mismatch of SiC relative to diamond.…”
Section: Epitaxial Silicon Carbide On Diamondmentioning
confidence: 58%
“…In addition, high electron mobility transistors made of AlGaN/GaN on diamond required thick buffer layers to construct operational devices. There is evidence that coherent interfaces are possible when diamond is grown onto SiC, but examples lie among typically unoriented polycrystalline diamond with poor interface characteristics. The growth of SiC onto diamond produces similar results, although it has been shown that a silicon buffer layer prior to SiC formation can enable the growth of oriented SiC by CVD . Domain matching epitaxy is a technique used to minimize the interface mismatch in high lattice misfit materials, but diamond’s extremely high lattice density prohibits such matching in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…That is why a procedure was developed in which the Si deposit is not wet etched. It allows performing both the buffer and CVD steps in the same run [4]. The recent results obtained with this procedure are detailed below.…”
Section: Resultsmentioning
confidence: 99%
“…SiC growth on diamond, the number of works is very limited with rather marginal success [1][2][3]. In a previous paper, the present authors reported the CVD growth of a single-crystalline 3C-SiC heteroepitaxial film on diamond (100) substrate [4]. This was achieved through the elaboration of an appropriate seeding SiC layer via a "silicidation" process, before the 3C-SiC CVD growth on diamond.…”
Section: Introductionmentioning
confidence: 99%